2009
DOI: 10.2214/ajr.09.2579
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Clinical Prostate Cancer: Role of Imaging

Abstract: Objective This article reviews a recent 2-day workshop on prostate cancer and imaging technology that was conducted by the Cancer Imaging Program of the National Cancer Institute. The workshop dealt with research trends and avenues for improving imaging and applications across the clinical spectrum of the disease. Conclusion After a summary of prostate cancer incidence and mortality, four main clinical challenges in prostate cancer treatment and management—diagnostic accuracy; risk stratification, initial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
127
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(129 citation statements)
references
References 97 publications
0
127
0
1
Order By: Relevance
“…21 The contributors were less convinced of the current role of imaging in the diagnostic pathway for these men. 22 There was overall agreement that multiparametric functional MRI and new TRUS techniques show promising results in multiple centers and publications in relation to characterizing men with prostate cancer and localizing their tumor. Based on these results, it is expected that these techniques will play a major role in the future for the selection, performance, and follow-up of patients with focal therapy.…”
Section: Assessment Of Patients Who May Be Candidates For Focal Therapymentioning
confidence: 74%
“…21 The contributors were less convinced of the current role of imaging in the diagnostic pathway for these men. 22 There was overall agreement that multiparametric functional MRI and new TRUS techniques show promising results in multiple centers and publications in relation to characterizing men with prostate cancer and localizing their tumor. Based on these results, it is expected that these techniques will play a major role in the future for the selection, performance, and follow-up of patients with focal therapy.…”
Section: Assessment Of Patients Who May Be Candidates For Focal Therapymentioning
confidence: 74%
“…A detectable or rising PSA level after therapy is considered to indicate biochemical recurrence, or "PSA failure," even when there are no symptoms or signs of locally recurrent or metastatic disease (1,2). By enabling selection of appropriate treatment, such as local salvage therapy or systemic therapy, imaging is useful for identifying locally recurrent or distant lesions when the PSA level is rising (3).…”
mentioning
confidence: 99%
“…Although preliminary studies have demonstrated that 11 C-acetate is a promising tracer for diagnosis of recurrent (8)(9)(10) or metastatic (11) prostate cancer, its use in primary diagnosis is less well established. In particular, the clinical role of 11 C-acetate in prostate cancer detection and staging is currently unclear (12,13). In vitro studies indicate that 11 C-acetate as a marker of enhanced lipid synthesis is appropriate for estimating the growth activity of tumor cells (14,15).…”
mentioning
confidence: 99%